Global discrimination of COVID-19 vaccine - Fariha Sohil; Muhammad Umair Sohail (Human Vaccines & Immunotherapeutics, 2022)
In the current pandemic, the global consensus between all stakeholders is the basic key to achieve success against COVID-19. In the last few months, global discrimination toward COVID-19 vaccine has continually been observed from the world’s leading stakeholders and that has led to instability toward the acceptability of COVID-19 vaccine.